Comparative Study Between Treatment with Cryotherapy Alone Versus Cryotherapy Plus Salicylic Acid Dressing for Planter Warts - Mahboob Ali, Muhammad Adeel Siddiqui, Majid Hussain, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To compare cryotherapy alone versus cryotherapy plus salicylic acid dressing for planter warts. Study Design: Randomized Control Trial Place and Duration of Study: Department of Dermatology, Combined Military Hospital, Abbottabad from 01 Mar, 2022 to 01 Aug, 2022. Methodology: Seventy participants were enlisted using a non-probability sequential sampling method and then randomly assigned to one of two groups. SPSS Version 23.0 was used for data entry, data entry, and data analysis. Results: As per comparison of efficacy between both groups, 20 (57.1%) patients in Group A (Cryotherapy Alone) showed effective results while in Group B (Cryotherapy plus Salicylic Acid), 30 (85.7%) patients showed effective results. P Value = 0.008. Conclusion: This study demonstrated that treatment of plantar warts with cryotherapy plus salicylic acid yielded significantly higher effective results in comparison to cryotherapy alone. Keywords: Planter Warts, Cryotherapy, Salicylic Acid